When you are asked about Carpal Tunnel Syndrome - Fariba Nasiri-Ziba (Iran University of Medical Sciences, 1993)
Carpal tunnel syndrome is known as an Industrial new epidemic. In many of jobs, the same motions of hand are repeated thousands of times a day.  Each day the number of people with the syndrome is increasing. Clerks, workers in food preparation and packaging, and secretaries of large supermarkets have a high risk for suffering from this syndrome. In fact, all people who flex and extend their wrist frequently in everyday work, are susceptible for carpal tunnel syndrome.